Biologically Active Quinoline‐Hydrazone Conjugates as Potential Trypanosoma cruzi DHFR‐TS Inhibitors: Docking, Molecular Dynamics, MM/PBSA and Drug‐Likeness Studies. Issue 12 (26th March 2021) - Yepes, Andrés F.; Quintero‐Saumeth, Jorge; Cardona‐Galeano, Wilson
Abstract: Chagas disease, is a chronic parasitic infection caused by protozoan parasites belonging to the genus Trypanosoma . New therapies for Chagas infections are urgently needed and represent a major challenge in medicinal chemistry. As part of these efforts, we recently designed and synthesized a series of molecular hybrids bearing quinoline and hydrazones moieties, with some of them displaying higher anti‐trypanosomal activities than benznidazole. Thus, the current work is focused on proposing a plausible action mechanism by which the most active compounds inhibited T. cruzi growth based on multilevel computational approaches. Docking showed that for the best binders there was a marked preference for binding to dihydrofolate reductase (DHFR) over cruzipain (around −9.0 kcal/mol). MD simulations not only validate the reliability of docking predictions, but showed that the ligand‐receptor complex was stable during the extended 50 ns simulations inside the active site (RMSD value of 1.96±0.34 Å). Furthermore, MM/PBSA studies also affirm the docking results. The MM/PBSA method revealed that most of the residues involved in the binding event are hydrophobic in nature, which are in accordance with those aminoacids essential in the DHFR function. Satisfactory pharmacokinetics profiles were also estimated for the top‐three active compounds. Finally, the results suggested that the active hybrids might act by inhibiting DHFR activity within T. cruzi, making them a privileged scaffold that can be used in future anti‐Chagas drug development. Abstract : Here, we investigated a plausible biochemical mechanism by which a series of quinoline‐hydrazone conjugates displayed great anti‐trypanosomal activity. To accomplish this, multilevel computational studies, including docking, molecular dynamic (MD) and MM/PBSA calculations was performed. A docking binding preference was observed against Tc ‐DHFR‐TS, while MD revealed that ligand‐receptor complex was stable within the Tc ‐DHFR‐TS active site. MM/PBSA procedure showed critical ligand‐interactions with essential residues for Tc ‐DHFR‐TS catalytic function. Optimal pharmacokinetics indices were founded for the title hybrids.